PEMBINAAN DAN PEMBERIAN BANTUAN KEPADA SEKOLAH PAUD (PENDIDIKAN ANAK USIA DINI) “PEDULI ANAK BANGSA” DI DESA PONDOK KUBANG, KECAMATAN PONDOK KUBANG, KABUPATEN BENGKULU TENGAH - Sri Hartanti (DHARMA RAFLESIA, 2018)
This community service activity was focused on the early childhood education school (PAUD or Pendidikan Anak Usia Dini), because this institution is now becoming a national public movement. Early childhood who are in the age range of 0 to 6 years old. At that time the chidren are experiencing a process of growth and development in various aspects, such as: physical, social, language and cognitive skills very quikly and is fundametal for their future. In fact, neurosccience experts call this developmental period of childhood as the golden age that between the age of 0 to 6 years old can give full attention by providing a good education for their children. Because of the importance of early childhood education, then this community service activity intended to provide guidance and aids to an early childhood education school (PAUD) whose condition is very poor, namely that in Pondok Kubang village.This PAUD was founded in 2008 on the initiative of the World Bank. However, since three years ago the World Bank has no longer given funds. Asd a result, this PAUD has become very poor. Almost all of the existing toys and books are now damaged. Event funds to provide incentives for teachers were not available. The metod used in this community service activity is an enhancement to the teachers by discussing and providing aids in the form of short-leg table to write, books of folklore, world story books, studying media, puzzles, and other game tools. All aids are very useful, both for teachers and students. Keywords: early childhood education, study aid material, national movement, development